2018
DOI: 10.1080/24748668.2018.1467995
|View full text |Cite
|
Sign up to set email alerts
|

Association between serve speed and court surface in tennis

Abstract: The aim of the study was to determine whether the serve speed differs between Grand Slam tournaments (GSTs) played on different court surfaces. The study was carried out for both men and women (n = 70-98) who participated in four of the GSTs in 2008, 2012 and 2016 (Australian Open, French Open, Wimbledon and US Open). The following serve-speed parameters were obtained from the official GST websites: the speed of the fastest serve (FS), the average speed of the first serve in a given match (S1) and the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
2
11
0
1
Order By: Relevance
“…By contrast, the greatest serve dominance in Grand Slam tournaments occurs at Wimbledon . The faster grass surface at Wimbledon encourages players to serve faster than they do at other Grand Slam tournaments (Vaverka, Nykodym, Hendl, Zhanel, & Zahradnik, 2018). This makes breaks of serve less frequent at Wimbledon and has resulted in some very long final sets at this tournaments (O'Donoghue, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the greatest serve dominance in Grand Slam tournaments occurs at Wimbledon . The faster grass surface at Wimbledon encourages players to serve faster than they do at other Grand Slam tournaments (Vaverka, Nykodym, Hendl, Zhanel, & Zahradnik, 2018). This makes breaks of serve less frequent at Wimbledon and has resulted in some very long final sets at this tournaments (O'Donoghue, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In all three years, the average speed of the first serve was found to be highest in Wimbledon (grass) for both men and women. The researchers reported that it would be possible to conclude from these results that players in Wimbledon are trying to achieve a higher first serve speed during the match than playing on other courts with different court surfaces (Vaverka et al, 2018). In a different study, significant differences were observed between the tournaments in both sexes in the aces, while aces reached the highest values in Australia Open in both men and women (Sánchez-Pay et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…It was observed that the biggest change was the increase in serve speed at the French Open and the serve speed continued to increase in all tournaments, such as aces (Cross and Pollard, 2009). However, the highest and lowest service speed values may vary depending on weather conditions such as sun, wind and temperature, or the use of different systems to measure or calibrate the service speed (Vaverka et al, 2018). In addition, O'Donoghue (2002) revealed that the speed of service is a number of factors that affect the proportion of points won on first and second service.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the relationship between the speed of the ball and various factors, such as the court surface, 1 impact height, 2,3 fatigue, and service accuracy. 4,5 Recently, studies have focused on clarifying mechanical phenomena (e.g.…”
Section: Introductionmentioning
confidence: 99%